Fiscal Vertical Imbalances and the Building of Subnational Financial Capacity - Chen, Mianwen; Zhang, Yating (Journal of Global Economy, Business and Finance, 2025)
Fiscal vertical imbalance is a key feature of the relationship between the central government and local authorities. This paper first provides a theoretical interpretation of the mechanism by which fiscal vertical imbalance affects local government fiscal capacity building, and then systematically introduces the process by which fiscal vertical imbalance influences the intensity of local fiscal capacity building. This process simultaneously exhibits both enhancing and weakening mechanisms. On the one hand, fiscal vertical imbalance may reinforce local governments’ efforts to enhance their own fiscal resources through mechanisms such as reliance on transfer payments and policy incentives. Conversely, fiscal vertical imbalance may also undermine local governments’ fiscal autonomy and sustainability by creating mismatches between fiscal authority and responsibilities and transmitting fiscal pressures. Based on this analysis, the paper proposes relevant policy implications.